Perceptions of Self-Evaluation Team Members Regarding Implementation Challenges: A Qualitative Study Based on the Experience of Self-Evaluation in Primary Schools in Southern Khamis Mushait - Al-Shahri, Sarah Ajlan (Journal of Educational and Psychological Sciences, 2025)
The current study aims to explore the challenges of implementing self-evaluation in primary schools in Southern Khamis Mushait from the perspectives of self-evaluation team members. The study adopted a qualitative methodology, specifically an interpretive research design, Qualitative data were collected through semi-structured interviews, A total of ten members of the self-evaluation teams participated in the study.The findings revealed that the most prominent challenges in implementing self-evaluation included the lack of infrastructure readiness and school facilities, the resistance to the developmental process by school staff, students, and parents, as well as the external evaluation teams' need for a better understanding of the public education system. The study recommended conducting a comprehensive assessment of the school environment and identifying the material and technical needs prior to the implementation of self-evaluation. It also emphasized the importance of awareness and training programs to prepare school staff, students, and parents and to familiarize them with the self-evaluation process.
Keywords: Challenges of Self-Evaluation; Primary Education; Self-Evaluation